Manufacturing Revolutions: Industrial Policy and Industrialization in South Korea - Nathan Lane (CESifo GmbH, 2024)
I study the impact of industrial policy on industrial development by considering an important episode during the East Asian miracle: South Korea's heavy and chemical industry (HCI) drive, 1973–1979. Based on newly assembled data, I use the introduction and termination of industrial policies to study their impacts during and after the intervention period. (1) I reveal that the heavy-chemical industrial policies promoted the expansion and dynamic comparative advantage of directly targeted industries. (2) Using variation in exposure to policies through the input-output network, I demonstrate that policy indirectly benefited down-stream users of targeted intermediates. (3) The benefits of HCI persisted even after it ended, some of which took time to manifest. These findings suggest that the temporary drive shifted Korean manufacturing into more advanced markets and supported durable change. This study helps clarify the lessons drawn from the East Asian growth miracle.
Keywords: L50; O14; O25; N60; 330; industrial policy; East Asian miracle; economic history; industrial development; Heavy-Chemical Industry Drive; Heavy and Chemical Industry Drive